Language Variation Discovered In The Interaction Between Buyer-Seller At Traditional Market - Munawaroh, Madinatul (Jurnal Ilmiah Mahasiswa Pendidikan [JIMEDU], 2021)
This study deals with the Language Variation found in The Interaction between buyer-seller at Traditional Market. The objective of this study was to describe (1) The types of language variation between buyer-seller in dialogue interaction at Traditional Market and to identify (2)The factors that influence language variation between buyer-seller in dialogue interaction at Traditional Market. The method in this research is descriptive qualitative method, where data is collected through recording techniques and note-taking techniques in the form of accurate conversation sin accordance with the natural characteristics of the informant sand then transcribed by the researcher in the form of text.The findings of research his the variations found in the interaction of buyers and sellers in traditional markets are variations in terms of speakers such as dialect;variations interms of usage,namely registers;variations in terms of formality such as casual style; as well as variations in terms of facilities, namely the oral style. This is dueto several factors found in the data namely,age, social status and gender.